Evaluation of a handheld creatinine measurement device for real-time determination of serum creatinine in radiology departments - Haneder, Stefan; Gutfleisch, Alexandra; Meier, Claudia; Brade, Joachim; Hannak, Dieter; Schönberg, Stefan; Michaely, Henrik J. M. (World journal of radiology, 2012)
Evaluation of a handheld creatinine measurement device for real-time determination of serum creatinine in radiology departments
Gesehen am 12.07.2018